Normativity, naturalization, and regulation - Adrián Scribano (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
<!--[if gte mso 9]> <![endif]--> From what “one must be”, through the accepted/accurate/acceptable shapes of bodies, to the emotionalization of moral, all of them make up the landscape portrayed by the articles hereby introduced. <!--[if gte mso 9]> Normal 0 21 false false false ES-AR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P